Morphogenesis and regeneration of whole plants of grapefruit (Citrus paradisi), sour orange (C-aurantium) and alemow (C-macrophylla) - Ghorbel, R.; Navarro, Luis; Durán-Vila, Núria (2017)
Studies were performed to define tissue culture techniques for morphogenesis and production of whole plants of grapefruit, sour orange and alemow. The NAA and BA concentrations to induce root formation, and bud and shoot regeneration on stem segments were determined. No roots formed in sour orange over the range of 0-162 mu M NAA. All species regenerated buds in response to BA but only those of alemow elongated sufficiently to root them. Of these, 84% rooted but only 16% of these plantlets survived weaning and transplanting to soil. Plants were consistently obtained by grafting apical tips from regenerated shoots and buds of the three species. Plants with successful grafts were transplanted to soil with survival rates of 90-100%.